How to Distinguish Smart Big Moves from Stupid Ones - Strebel, Paul (Institutional Knowledge at Singapore Management University, 2009)
When top executives undertake big moves – dramatic shifts in strategic direction – their decisions can make or break a company. This paper aims to offer a methodology for cutting the risks of making a catastrophic misstep. To avoid a corporate disaster and increase the chances of a smart and ultimately successful big move the paper raises six critical questions that must be answered honestly and unequivocally by managers. The research indicates that there are five classic types of big move, each corresponding to a different position on the corporate performance curve: finding a new game; going for growth; getting into shape; relaunching growth; and restoring profitability. The paper outlines the ego traps of each big move and how to avoid them. By defining the critical six questions and revealing the ego traps and how to avoid them the paper provides a valuable learning guide and checklist for top management.